Implementation of model based transferable belief model for pattern recognition and classification - Durukan, Gürcan (My University, 2020)
Bu tezde, Aktarılabilir İnanç Modelinden türetilmiş olan Model Tabanlı Sınıflandırıcı gemilerin otomatik olarak sınıflandırılması amacıyla gerçeklenmiştir. Aktarılabilir İnanç Modeli, Bayesian Teorisi, Bulanık Küme Teorisi, Genel Olasılık Teorisi gibi yöntemlere kıyasla kanıt eksikliğinden doğan belirsizliği daha iyi modelleyebilmektedir. Aktarılabilir İnanç Modeli, farklı kaynaklardan elde edilen bilgilerin kaynaştırılmasına imkan vermektedir. Ayrıca, kaynaştırılacak bilgiler arasında çelişki olup olmadığı Aktarılabilir İnanç Modeli kullanılarak belirlenebilmektedir. Farklı bilgi kaynaklarından gelen çelişmeyen bilgiler kaynaştırılacak yüksek sınıflandırma doğruluğu elde edilmiştir. Model Tabanlı Sınıflandırıcının sınıflandırma doğruluğu oluşturulan yapay veritabanları üzerinde gerçeklenen benzetimlerle belirlenmiştir.

In this thesis, the Model Based Classifier derived from the Transferable Belief Model is implemented for the purpose of automatic ship classification. The Transferable Belief Model models uncertainty caused by lack of evidence better compared to other approaches such as Bayesian Theory, Fuzzy Set Theory and General Probability Theory. The Transferable Belief Model allows one to combine information obtained from different sources. In addition, whether a conflict exists among different information sources or not can be determined by using the Transferable Belief Model. As a result, non-conflicting information coming from different information sources are combined to get high classification accuracy. Artificial learning sets are used in the simulations to obtain the classification accuracy of the Model Based Classifier.
Keywords: Aktarılabilir İnanç Fonksiyonu; Belief Function Theory; Classification; Conflict Detection; Çelişki Tespiti Pattern Recognition; Electric engineering; Electronics engineering; Elektrik mühendisliği; Elektronik mühendisliği; İnanç Fonksiyonu Teorisi; Örüntü Tanıma; Sınıflandırma; Transferable Belief Model